Women in the Bible - Clark-Soles, Jaime (Interpretation: Resources for the Use of Scripture in the Church, 2020)
Women in the Bible investigates how women are presented in Scripture, taking into account cultural views of both ancient societies as well as our own. Jaime Clark-Soles treats well-known biblical women from fresh perspectives, highlights women who have been ignored, and recovers those who have been erased from historical memory.